2016 IEEE International Symposium on Mixed and Augmented Reality (ISMAR) 2016
DOI: 10.1109/ismar.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Medium Wrap Freehand Virtual Object Grasping in Exocentric Mixed Reality

Abstract: This article presents an analysis into the accuracy and problems of freehand grasping in exocentric Mixed Reality (MR). We report on two experiments (1710 grasps) which quantify the influence different virtual object shape, size and position has on the most common physical grasp, a medium wrap. We propose two methods for grasp measurement, namely, the Grasp Aperture (GAp) and Grasp Displacement (GDisp). Controlled laboratory conditions are used where 30 right-handed participants attempt to recreate a medium wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…We then compared these categories across grasping metrics for each experiment condition and show that there are significant differences between object categories for grasp metrics, showing that virtual object shape influences grasping approach in VR. A similar result was observed in Mixed Reality, namely that object shape and size influenced the grasping approach [2]. Further, we compared experiment conditions for each object category and found that there were no differences between conditions for grasp metrics.…”
Section: Object Categoriessupporting
confidence: 79%
See 3 more Smart Citations
“…We then compared these categories across grasping metrics for each experiment condition and show that there are significant differences between object categories for grasp metrics, showing that virtual object shape influences grasping approach in VR. A similar result was observed in Mixed Reality, namely that object shape and size influenced the grasping approach [2]. Further, we compared experiment conditions for each object category and found that there were no differences between conditions for grasp metrics.…”
Section: Object Categoriessupporting
confidence: 79%
“…Recent VR systems use the hand, the most powerful tool through which we interact with the surrounding world, as the main interaction tool [1]. However, when creating bare hand interactive systems, aiming to provide seamless and intuitive interactions, researchers have focused on a natural approach known as grasping [2].…”
Section: Interaction In Virtual Realitymentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers are currently evolving gesture interactions into physical interactions, thus, completely mimicking the interaction performed in the real world, into AR environments [46,49]. The work of Al-Kalbani et al [4] and [5] have sought to understand the complex nature of the human grasp for freehand interaction and defined the problems associated with grasping objects in AR, Ciodota et al [15] evaluated the application of grasps in AR and also Swan et al [51] evaluated the problems associated with representing and reaching the true located space of augmented objects.…”
Section: Interaction Approachesmentioning
confidence: 99%